Pelatihan Praktek Pembuatan Laporan Keuangan dan Perpajakan UMKM Provinsi Riau - Irman, Mimelientesa; Darmasari, Ria; Santoso, Pamuji Hari; Okalesa, Okalesa; Yusrizal, Yusrizal; Anton, Anton (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the era of globalization and technological advancement, the role of MSMEs in the economy is becoming increasingly important. However, the inability of MSMEs to prepare financial reports and fulfill their tax obligations results in difficulties accessing capital. MSMEs are unable to meet the requirements for obtaining capital through banks or other financial institutions. The purpose of this community service is to provide literacy to individual taxpayers (MSMEs) who have not properly fulfilled their tax obligations, particularly regarding the changes from Government Regulation 23 of 2018 to the 2020 Harmonization of Tax Regulations (HPP) Law. The methods used were counseling and outreach regarding taxation and financial reporting for MSMEs. The results of the discussion revealed that the non-taxable gross turnover limit is IDR 500,000,000, in accordance with the 2020 Harmonization of Tax Regulations (HPP) Law.